PENGARUH FAKTOR-FAKTOR ANTECEDENT DAN CONSEQUENCE PERCEIVED VALUE TRUST IN A BRAND DAN CUSTOMER SATISFACTION PADA UNIVERSITAS WIJAYAKUSUMA PURWOKERTO - Kabul Budiyono; Suwarno; Hening Riyadiningsih; Heru Cahyo (Majalah Imiah Manajemen & Bisnis, 2020)
This research was conducted at the Faculty of Economics UNWIKU Purwokerto titled: "Effect of Experiential Marketing Customer Satisfaction, Confidence, Commitment and Behavior Intention At the Faculty of Economics Unwiku Purwokerto" The purpose of this study was to determine the effect Experiental Marketing, to customer satisfaction, trust, commitment and behavior intention in the Faculty of Economics UNWIKU Purwokerto. The analytical tool used Structural Equation Modeling (SEM). From the research and data analysis we concluded that :Variable marketing Experental positive and significant effect on behavioral intention, the better the marketing experental increasing behavioral intention. Experental marketing positive and significant impact on consumer satisfaction, the better experental marketing increases consumer satisfaction. Consumer satisfaction is positive and significant impact on the trust, the better the customer satisfaction is increasing confidence. Belief positive and significant effect on behavioral intention, the better keprcayaan increasing behavioral intention. Consumer satisfaction is positive and significant effect on behavioral intention, the better the customer satisfaction has increased behavioral intention. Consumer satisfaction is positive and significant effect on commitment, the higher the customer satisfaction has increased as well commitment. Commitment positive and significant effect on behavioral intention, the higher the commitment is increasing as well behavioral intention. Based on the conclusion, where experental marketing has a significant influence on consumer satisfaction and also to behavioral intention, then the Faculty of Economics UNWIKU need to examine more deeply or redesigning policies connection in this case is related to experiential marketing including development of learning processes and administrative processes with the standard of service in the management of the college